A review of surface wipe sampling compared to biologic monitoring for occupational exposure to antineoplastic drugs. Issue 3 (4th March 2017) - Kibby, Thomas
ABSTRACT: The potential for adverse health effects from occupational exposure to antineoplastic drugs (AD) is well known. Control measures recommended by the NIOSH Alert [3] include medical and biologic monitoring, and environmental monitoring where available. At present no guidelines or published best practices exist to guide EHS managers on how to carry out this biologic or environmental monitoring. Studies investigating surface wipe sampling for AD have been numerous in the past decade, but very limited research exists to correlate surface contamination with actual absorption by pharmacists and nurses. This article reviews the studies with concurrent surface wipe sampling and urine monitoring for the same AD, and tests their correlation. Methodologic limitations are reviewed. Twenty-one studies were identified that concurrently measured surface contamination by AD by wipe sampling and AD absorption by urine monitoring. Two studies directly evaluated the AD by wipe sampling and urine levels and neither found a statistically significant correlation. Six studies reported a decrease in both surface and urine levels following interventions to reduce contamination or exposure. Only one study directly evaluated the personal protective equipment and handling techniques employed by the studied workers, which can be viewed as a major confounder of absorption. While no statistically significant correlation was found between wipe sampling and urine monitoring for AD, decreases in urine and wipe levels following interventions to reduce exposure were noted. Limitations in the data and recommendations for future research are reviewed.